A Novel Halogen Bond Acceptor: 1-(4-Pyridyl)-4-Thiopyridine (PTP) Zwitterion - Xin Ding (Crystals, 2020)
Sulfur is a widely used halogen bond (XB) acceptor, but only a limited number of neutral XB acceptors with bifurcated sp3-S sites have been reported. In this work a new bidentate XB acceptor, 1-(4-pyridyl)-4-thiopyridine (PTP), which combines sp3-S and sp2-N acceptor sites, is introduced. Three halogen bonded cocrystals were obtained by using 1,4-diiodobenzene (DIB), 1,4-diiodotetrafluorobenzene (DIFB), and iodopentafluorobenzene (IPFB) as XB donors and PTP as acceptor. The structures of the cocrystals showed some XB selectivity between the S and N donors in PTP. However, the limited contribution of XB to the overall molecular packing in these three cocrystals and the results from DSC measurements clearly point out the synergetic influence and interplay of all noncovalent interactions in crystal packing of these compounds.